2020
DOI: 10.1002/sce.21568
|View full text |Cite
|
Sign up to set email alerts
|

Truth, success, and faith: Novice teachers’ perceptions of what's at risk in responsive teaching in science

Abstract: Responsive teaching-or teaching that builds from the "seeds of science" in student thinking-is depicted in STEM education literature as both important and challenging. U.S. science education reform has been calling for teachers to enact instruction that attends to and takes up the substance of students' STEM ideas; however, responsive teaching represents a substantial shift from the current state of affairs in most U.S. classrooms, where content is often presented authoritatively as facts, definitions, and alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…While the focus on vocabulary in literacy instruction tends to be dominant in practice, a different approach focusing on reading-and writing-to-learn pedagogies is influenced or driven by education researchers (For a comprehensive review, see Pearson et al, 2010;Wright et al, 2016;Yang, Kuo, & Jiang, 2020). Examples of these pedagogies include Seeds of Science, Roots of Reading (Barber, Pearson, & Cervetti, 2006;Robertson & Elliott, 2020), Concept-Oriented Reading Instruction (Brown & Concannon, 2016;Guthrie, Wigfield, & Perencevich, 2004), Science Writing Heuristic (Hand, Shelley, Laugerman, Fostvedt, & Therrien, 2018), and Budding Science and Literacy Program (Sørvik et al, 2015).…”
mentioning
confidence: 99%
“…While the focus on vocabulary in literacy instruction tends to be dominant in practice, a different approach focusing on reading-and writing-to-learn pedagogies is influenced or driven by education researchers (For a comprehensive review, see Pearson et al, 2010;Wright et al, 2016;Yang, Kuo, & Jiang, 2020). Examples of these pedagogies include Seeds of Science, Roots of Reading (Barber, Pearson, & Cervetti, 2006;Robertson & Elliott, 2020), Concept-Oriented Reading Instruction (Brown & Concannon, 2016;Guthrie, Wigfield, & Perencevich, 2004), Science Writing Heuristic (Hand, Shelley, Laugerman, Fostvedt, & Therrien, 2018), and Budding Science and Literacy Program (Sørvik et al, 2015).…”
mentioning
confidence: 99%
“…There is preliminary evidence that they might not be able to. Robertson and Elliot ( 2020 ) found that novice physics instructors showed a hesitance to teach responsively, i.e., building on students’ beginning ideas without evaluation. An instructor cited concerns that they would risk damaging what students took to be the objective, impartial truth (Robertson & Elliot, 2020 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…We agree with Ladson-Billings ( 1997 ) that “[Culture] informs all human thought and activity and cannot be suspended as human beings interact with particular subject matters or domains of learning” (p. 700). While education researchers have expressed that the teaching of STEM subjects is an inherently political activity (Gutiérrez, 2017 ; Mendick, 2011 ; Prescod-Weinstein, 2020 ), many STEM instructors still express beliefs that their fields are objective and free of culture (Miller-Young et al, 2018 ; Robertson & Elliot, 2020 ). Little research has investigated how or why STEM instructors teach with CRP at HSIs, and how beliefs about the nature of disciplinary knowledge might play a role in those decisions.…”
Section: Introductionmentioning
confidence: 99%
“…One is that they are reticent to elicit the ideas of their students because they fear that some ideas that are surfaced may be at odds with scientifically accepted ideas, and that students will end up accepting those incorrect ideas (Maskiewicz, 2015; Miller et al, 2018). Another concern that is voiced is that the time required to elicit and attend to student ideas conflicts with the goals of curricular coverage (Levin, 2008), and the time necessary to respond to students' ideas will result in the sacrifice of content covered (Robertson & Atkins Elliott, 2020). While common concerns, this way of thinking is antithetical to the modern vision of science teaching and learning as represented in the Next Generation Science Standards (NGSS Lead States, 2013) in the United States.…”
Section: Introductionmentioning
confidence: 99%